The influence of demographic factors towards tax compliance in Universiti Utara Malaysia - Abdullah, Siti Alida John (Universiti Utara Malaysia, 2002)
Taxes are the most important source of revenue to most countries including Malaysia in order to fund the many functions of a modern democratic state. Everybody must pay tax in order to fulfill his or her responsibilities to the state. Recently, Malaysia has introduced Self-Assessment System whereby the taxpayer is responsible to calculate, assess and pay their taxes to the Inland Revenue Board (IRB).The implication of this introduction is that taxpayers must be more aware of any changes in the tax codes. The objectives of this study is to determine the influence of demographic factors on tax compliance attitudes, taxpayers perceptions on tax fairness and taxpayers perceptions on the simplicity/complexity of the individual income tax structure. This study is focused only on wage earners or employees and the population is UUM staffs who have been paying income tax through the Scheduler Tax Deduction Scheme. Random sampling method is used to select 250 sample from a list of 675 academic and non-academic staff. The findings of this study shows that there are no significant differences in terms of the tax variables between gender, age groups, income levels, profession (academician and non-academician) and highest academic qualification (from SPM to First Degree and those with Masters and Doctorates). It is found that generally UUM staff considered the personal income tax system in Malaysia as relatively fair especially when lower income group is exempted or pays lower tax rates.There are also significant differences between gender, income groups and profession regarding the exemption. There are also significant differences between gender and perceptions towards tax complexity among the respondents. This study also found that there is weak positive relationship between perceptions regarding tax fairness and tax compliance. There is also a weak negative relationship between perceived tax fairness and perceived tax structure complexity while there is no significant correlation between perceived tax complexity and compliance attitudes. The population of this study restricted only to the UUM staff and the results may not represent the whole Malaysian taxpayers. Further study could extend the population to both wage earners and self-employed taxpayers.